2001
DOI: 10.1002/mus.1181
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for phrenic nerve latency in children

Abstract: Data derived from detailed studies of normal phrenic nerve latency in a large group of children are presented. They highlight the major differences between the three previously published studies of normal children. Phrenic nerve latency shows a curvilinear relationship with age, averaging 6.0 ms at 0-6 months, falling to 4.8 ms between 1 and 2 years, then rising to 6.3 ms between 10 and 18 years of age. These data represent the largest published study on normal phrenic nerve latency in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The phrenic nerve latencies recorded in the current study are similar to those reported previously [15,24,25]. Surface electrodes record activity from the costal component of the diaphragm while the oesophageal EMG records activity from the crural portion of the diaphragm [26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The phrenic nerve latencies recorded in the current study are similar to those reported previously [15,24,25]. Surface electrodes record activity from the costal component of the diaphragm while the oesophageal EMG records activity from the crural portion of the diaphragm [26].…”
Section: Discussionsupporting
confidence: 86%
“…At least 10 stimulations at maximum stimulator output were made on each side and the mean PNL and CMAP amplitude recorded. The normal range for PNL in this age group was taken as 2.9-9.1 ms [15] The supramaximality of the stimuli was assessed by examining the mean CMAP amplitude and PNL over the range 80, 85, 90, 95 and 100% of stimulator PAEDIATRIC RESPIRATORY DISEASE Z. KASSIM ET AL.…”
Section: Protocolmentioning
confidence: 99%